Analisis Strategi Pemasaran Terhadap Pendapatan Pada UKM Jamur Tiram di Desa Bandar Labuhan - Suri Ambar Wati; Ova Novi Irama (ARBITRASE: Journal of Economics and Accounting, 2022)
Micro,small and medium enterprises(MSMEs)are one of the economic entities whose exsistence continues to be encouraged by the government,because they ‘can absorb labor,can reduce unemloyment and also increase people’income.port of cape morawa sub-district.this research uses a descriptive method,namely a case study that produces descriptive date set forth in words.the date collection technique in this study was carried out through a process of direct interviews with predetermined key informants.this research was carried out in the village of bandar labuhan ,which produces and market oyster mushrooms in Tanjung Morawa district,this research is a descriptive research that aims to determine the marketing strategy.this study was analyzed using SWOT analysis.technical data analysis was carried out simultaneously starting from the process of data reduction,data presentation to verification or drawing conclussions.The result of the study show that the Oyster MushroomBusiness Product Marketing Strategy,which belongs to this home owned business,has a focus on marketing to increase revvenue for the resulting Oyster Mushroom product,starting at the level of product quality,price,promotion and product distribution